A longitudinal evaluation of a survivor-mentor program for child survivors of sex trafficking in the United States. (February 2020) - Rothman, Emily F.; Preis, Sarah R.; Bright, Katherine; Paruk, Jennifer; Bair-Merritt, Megan; Farrell, Amy
Abstract: Background: Commercial sexual exploitation (CSE) of children is a significant public health and criminal justice problem, but there are few evaluated models of CSE mentorship service. Objectives: To assess whether youth who participated in a CSE survivor-mentor program evidenced changes in CSE victimization, dating abuse victimization, health, delinquency, social support, and coping during the year following their enrollment in the program. Participants: 41 youth who were CSE-experienced at baseline (72%) or determined very high risk, 11–18 years old, 95% female, 58% heterosexual, 29% White, 29% Hispanic, and 42% other races/ethnicities. Setting: An urban city in the Northeast United States. Methods: We used a one-group repeated measures design and a GEE analysis. Data were collected at baseline, six months after baseline (71% follow-up) and 12 months after baseline (68% follow-up). Results: At baseline 72% could be characterized as CSE-experienced, while at 6 months the percentage decreased to 24% (p < 0.001) and at 12 months to 14% (p < 0.001). After 6 months of receiving survivor-mentor services, youth were less likely to have experienced CSE, engaged in sexually explicit behavior (SEB), used illicit drugs, engaged in delinquent behavior, been arrested or detained by police, and they had better social support and coping skills. After 12 months, youth were less likely to have experienced CSE, to have engaged in delinquent behavior, be arrested or detained by police, and had improved coping skills. Conclusion: Findings demonstrate that youth who received survivor-mentor services from MLMC experienced improved well-being and less drug use, delinquent behavior, and exploitation.